3D Printed Electrochromic Supercapacitors with Ultrahigh Mechanical Strength and Energy Density. Issue 41 (12th September 2021) - Chang, Peng; Mei, Hui; Zhang, Minggang; Zhao, Yu; Wang, Xiao; Cheng, Laifei; Zhang, Litong
Abstract: With the accelerating update of advanced electronic gadgets, a great deal of attention is being paid today to the function integration and intelligent design of electronic devices. Herein, a novel kind of multitasking 3D oxygen‐deficient WO3– x ∙ 2H2 O/Ag/ceramic microscaffolds, possessing simultaneous giant energy density, ultrahigh mechanical strength, and reversible electrochromic performance is proposed, and fabricated by a 3D printing technique. The ceramic microscaffolds ensure outstanding mechanical strength and stability, the topology optimized porous lattice structure provides developed surface area for coloration as well as abundant easily accessible channels for rapid ion transportation, and the bifunctional oxygen‐defective pseudomaterials enable the large areal capacity and impressive electrochromic performance. As a result, this 3D‐printed multitasking microscaffolds simultaneously perform structure‐designable, electrochromic, compression resistant, and energy storage functions, behaving with true 3D structure with tailorable curvatures, excellent compressive strength (61.9 MPa), large color variations (>145% in b * value), good aesthetic visual quality as well as exciting electrochemical performances for energy storage including ultrahigh areal capacitance (10.05 F cm −2 at 5 mA cm −2 ), record‐high energy density (0.60 mWh cm −2 ), and superior long‐term cycling stability (88.6% capacity retention after 10 000 cycles). This work opens up the possibility for high‐performance multi‐functional coupling structural materials and integrated systems. Abstract : A new class of multitasking 3D defect‐enriched WO3– x ∙ 2H2 O/Ag/SiOC ceramic microscaffolds is fabricated by 3D printing technique. Benefiting from hierarchical nanostructures of WO3– x ∙ 2H2 O and well‐designed high‐surface‐area periodic cellular architectures, the assembled electrochromic supercapacitors manifest record‐high areal capacitance, giant energy density, ultrahigh mechanical strength and reversible electrochromic performance, paving the way for high‐performance multifunctional coupling structural materials and integrated systems.